2023
DOI: 10.3390/pediatric15020032
|View full text |Cite
|
Sign up to set email alerts
|

Negative Outcomes Associated with Medication in Neonates on Parenteral Nutrition Therapy

Abstract: Objective: In Ecuador, studies on clinical daily practice problems focused on parenteral nutrition in neonates are scarce. Therefore, this research aimed to identify negative results associated with medications (NRAM) in neonates with parenteral nutrition (PN) in a third-level hospital in Ecuador. Material and methods: An observational, prospective, descriptive study was designed in the neonatology area of a tertiary-level public hospital, where, for over four months, the medical records, PN prescriptions, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Leopoldino et al conducted a longitudinal study in Brazil to assess possible predictors of TRPs in NICU, gestational age, certain medications (alprostadil, antibiotics, and omeprazole) and neurological, cardiac, and renal diseases were risk factors for TRPs in NICUs [ 24 ], but neonates on PN were excluded from the latter study. In a recent prospective study of 78 patients, Diaz et al, identified an association between prematurity, number of medications, parenteral nutrition time and negative results associated with medications [ 25 ]. Our study showed that most neonates are presented with prematurity so we cannot assess this association.…”
Section: Discussionmentioning
confidence: 99%
“…Leopoldino et al conducted a longitudinal study in Brazil to assess possible predictors of TRPs in NICU, gestational age, certain medications (alprostadil, antibiotics, and omeprazole) and neurological, cardiac, and renal diseases were risk factors for TRPs in NICUs [ 24 ], but neonates on PN were excluded from the latter study. In a recent prospective study of 78 patients, Diaz et al, identified an association between prematurity, number of medications, parenteral nutrition time and negative results associated with medications [ 25 ]. Our study showed that most neonates are presented with prematurity so we cannot assess this association.…”
Section: Discussionmentioning
confidence: 99%